Necrotizing enterocolitis and mortality after transfusion of ABO non‐identical blood. Issue 11 (6th September 2021) - Parvizian, Michael K.; Barty, Rebecca; Heddle, Nancy M.; Li, Na; McDougall, Tara; Mukerji, Amit; Fusch, Christoph; Solh, Ziad
Abstract: Background: The relationship between ABO non‐identical transfusion and the outcomes of necrotizing enterocolitis (NEC), and all‐cause mortality in very‐low birth weight (VLBW) neonates receiving red blood cell transfusion is unknown. Study design and methods: A retrospective multicenter cohort study was conducted in VLBW neonates in neonatal intensive care units between 2004 and 2016. VLBW (≤1500 grams) neonates were followed until discharge or in‐hospital death. The primary exposure was ABO group. Secondary exposures included platelet count, plasma transfusions, and maternal ABO group. Outcome measures were NEC (defined as Bell stage ≥ 2) and all‐cause mortality. Time‐dependent Cox regression models with competing risks were used to investigate factors associated with NEC and mortality. Results: Thousand and sixteen neonates were included with 10.8% developing NEC ( n = 110) and 14.1% mortality ( n = 143). Platelet count (hazard ratio [HR] = 0.995; 95% confidence interval [CI]: 0.922–0.998) and number of plasma transfusions (HR = 2.908; 95% CI:1.265–6.682) were associated with NEC, while ABO group (non‐O vs. O) was not (HR = 0.761; 95% CI: 0.393–1.471). Higher all‐cause mortality occurred in neonates without NEC who were non‐O compared with O (HR = 17.5; 95% CI: 1.784–171.692), but not in neonates with NEC (HR = 1.112; 95% CI: 0.142–8.841). Plasma transfusion was associated with increased mortality in both groups. Discussion: ABO non‐identical transfusion was not associated with NEC or mortality in neonates with NEC. It was associated with increased mortality in neonates without NEC. As many neonatal intensive care units transfuse only O group blood as routine practice, future trials are needed to investigate the association between this practice and neonatal mortality.